(untitled) (Jurnal Bahasa, 2012)
This study focuses on verbs used in the slogans of facial beauty products. This study employs the componential analysis of meaning theory which was founded by Nida, E.A (1975). The analysis uses binary semantic features [+] and [-] to show the similarities and dissimilarities in components of meaning between verbs. Using these [+] and [-] features, the accuracy of verbs used in the slogan is highlighted. 45 slogans were used in the data. From 45 slogans, 66 verbs were found to have been used. Analysis shows two types of verbs labelled either as verbs with specific function and general verbs. Verbs with specific function refers to verb used with collocations while those without are general verbs. Analysis shows that only five verbs (7.6 percent) are verbs with specific function while 61 (92.4 percent) of the verbs relating to facial beauty products were general verbs. Keywords: verbs with specific function, general verbs, collocation, semantic features, synonyms